2020
DOI: 10.1088/1674-1056/ab7907
|View full text |Cite
|
Sign up to set email alerts
|

Controlling electron collision by counterrotating circular two-color laser fields*

Abstract: Electron collision as well as its controlling lies in the core of study on nonsequential double ionization (NSDI). A single collision occurred in a convergent time is important to disclose the essential features of the electron correlation. However, it is difficult to form such a collision. By using counterrotating circular two-color (CRTC) laser fields, we show that a single electron collision can be achieved in a convergent time and a net electron correlation is set up within the sub-femtosecond time scale i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…[5] The ultrashort attosecond pulses can also induce electron charge migration, thus offering the possibility for probing the molecular structure and imaging the molecular reactions. [6][7][8] In the research, a variety of pulses and their combinations have been used to explore electron dynamics, including the high-order harmonic generation (HHG), [9][10][11][12][13][14] nonsequential double ionization (NSDI), [15][16][17][18] and the photoelectron momentum distribution (PMD). [19][20][21][22][23] Recently it was found that single ionization of atom by two oppositely circularly polarized, time-delayed attosecond pulses produce vortex patterns in PMDs, [24][25][26][27] which are sensitive to the time delay between the pulses, their handedness, and their relative phase.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The ultrashort attosecond pulses can also induce electron charge migration, thus offering the possibility for probing the molecular structure and imaging the molecular reactions. [6][7][8] In the research, a variety of pulses and their combinations have been used to explore electron dynamics, including the high-order harmonic generation (HHG), [9][10][11][12][13][14] nonsequential double ionization (NSDI), [15][16][17][18] and the photoelectron momentum distribution (PMD). [19][20][21][22][23] Recently it was found that single ionization of atom by two oppositely circularly polarized, time-delayed attosecond pulses produce vortex patterns in PMDs, [24][25][26][27] which are sensitive to the time delay between the pulses, their handedness, and their relative phase.…”
Section: Introductionmentioning
confidence: 99%